Answer:
Let p(x) = x3 + ax2 + bx +6
(x-2) is a factor of the polynomial x3 + ax2 + b x +6
p(2) = 0
p(2) = 23 + a.22 + b.2 +6 =8+4a+2b+6 =14+ 4a+ 2b = 0
7 +2 a +b = 0
b = - 7 -2a -(i)
x3 + ax2 + bx +6 when divided by (x-3) leaves remainder 3.
p(3) = 3
p(3) = 33 + a.32 + b.3 +6= 27+9a +3b +6 =33+9a+3b = 3
11+3a +b =1 => 3a+b =-10 => b= -10-3a -(ii)
Equating the value of b from (ii) and (i) , we have
(- 7 -2a) = (-10 - 3a)
a = -3
Substituting a = -3 in (i), we get
b = - 7 -2(-3) = -7 + 6 = -1
Thus the values of a and b are -3 and -1 respectively.
Step-by-step explanation:
Put the event number at the bottom where it say event
5 dollars per hour
because 15 divided by 3 is 5.
Answer:
![5g+15](https://tex.z-dn.net/?f=5g%2B15)
Step-by-step explanation:
To solve this question, we will first expand the expression using the distributive rule: ![x(y+z)=xy+xz](https://tex.z-dn.net/?f=x%28y%2Bz%29%3Dxy%2Bxz)
Therefore:
![2g+3(g+5)=2g+3*g+3*5](https://tex.z-dn.net/?f=2g%2B3%28g%2B5%29%3D2g%2B3%2Ag%2B3%2A5)
Simplify:
![2g+3g+15](https://tex.z-dn.net/?f=2g%2B3g%2B15)
Add up like terms:
![5g+15](https://tex.z-dn.net/?f=5g%2B15)